The Implementation of Influencer Marketing Strategies by Bakso Pikat to Increase Brand Awareness through TikTok - Rizqi Hadratun Nisa; Sovia Sitta Sari (Jogjakarta Communication Conference (JCC), 2026)
Influencer marketing strategies are increasingly developing as a digital marketing communication approach, especially for new culinary brands that utilize algorithm-based platforms such as TikTok. However, its implementation is still dominated by measurements of reach, impressions, and engagement, without integrating exploratory behavior indicators such as click-through rate (CTR) into the process of building brand awareness. This study aims to analyze the implementation of influencer marketing strategies by Bakso Pikat to increase brand awareness on the TikTok platform. This study uses a descriptive qualitative method with a case study approach. Data were collected through in-depth interviews with the owner, marketing manager, digital marketer, and two consumers of Bakso Pikat, which were reinforced with documentation of promotional content and TikTok account insights. The findings show that an influencer marketing strategy implemented systematically through collaborations with macro, micro, and nano-influencer along with the integration of click-through rate (CTR) elements via call-to-action can encourage a shift in audience behavior from the interest phase to the search phase in the AISAS model. Click-through rate (CTR) serves as an indicator of active audience engagement that facilitates information exploration regarding business profiles and locations. This strategy successfully contributes to brand awareness at the levels of brand recognition and brand recall within a specific product category. The study demonstrates that behavioral indicators such as click-through rate (CTR), can be used as strategic tools to building brand awareness for a new culinary brand on the TikTok platform.